Constrained statistical inference inequality, order, and shape restrictions - Silvapulle Mervyn J; Sen Pranab K (New Jersey John Wiley, 2005)
This volumes focuses on the theory of statistical inference under inequality constraints, providing a unified and up-to-date treatment of the methodology. The scope of applications of the presented methodology and theory in different fields is clearly il
Keywords: Multivariate analysis